Preventive therapy with citalopram added to a beta blocker does not result in quality-of-life improvement in patients with episodic migraine - Juan Carlos García-Monco; Ane Anton Ladislao; Marian Gómez-Beldarrain; David Anguizola-Tamayo; Ana Pinedo-Brochado; Aida Rodriguez-Sainz (SAGE Publishing, 2018)
Background: The quality of life of migraine patients, particularly mental domains, is severely diminished despite the preventive therapies available. We aimed to evaluate whether citalopram plus nadolol is superior to nadolol alone in terms of quality of life (QOL) in migraine patients. Methods: Adult patients with episodic migraine (≥ 3 headache days per month) were allocated by simple randomization to nadolol 40 mg daily plus citalopram 10 mg daily or to nadolol alone. Baseline visit confirmed the entry criteria and patients filled out a generic QOL (SF-36) as well a migraine-specific questionnaire (MSQoL), a measure of migraine-related disability (MIDAS), a headache calendar and Beck inventory for depression and anxiety. This battery was again completed after 16 weeks of therapy. Results: A total of 92 patients from a general neurology clinic completed the study, 85% females with migraine without aura. Fourty-four (47.83%) patients were allocated to nadolol therapy, and 48 (52.17%) to the combination of nadolol plus citalopram. After therapy, both groups had a similar gain in quality of life (SF-36 and MSQOL), but combination therapy was not superior to nadolol. Despite this improvement, all SF-36 domains remained below the population norms in both groups. Conclusion: Adding systematically citalopram 10 mg daily to a conventional migraine preventive drug (nadolol) does not result in an additional improvement in the QOL of migraine patients.